110. Tongue's motor evoked potentials in the diagnosis of Primary Lateral Sclerosis (PLS): Preliminary report. Issue 4 (April 2016) - Parenti, L.; Bocci, T.; Barlosci, D.; Vannini, B.; Giorli, E.; Di Rollo, A.; Mazzucchi, S.; Sartucci, F.
Abstract : Primary Lateral Sclerosis (PLS) is an adult-onset neurodegenerative disorder due to a selective loss of precentral pyramidal neurons. Our purpose was to evaluate preferential impairment of pyramidal tract to bulbar muscles in patients with PLS and identify a valuable electrophysiological method to help clinicians in the differential diagnosis from Amyotrophic Lateral Sclerosis (ALS). We recorded Motor Evoked Potentials (MEPs) from tongue and anterior tibialis muscles in six patients with PLS and compared the results, in terms of Central Motor Conduction Time (CMCT), amplitude of MEPs and duration of controlateral silent period (cSP), with those obtained both from ten age-matched healthy volunteers and ten patients affected by ALS. For lower limbs, CMCT resulted significantly increased in PLS and ALS samples compared with healthy subjects ( p  < 0.01); we did not disclose any difference between ALS and PLS groups ( p  = 0.417). Instead for tongue's recordings, CMCT, absolute amplitude of MEPs and cSP were significantly altered in PLS patients towards both ALS patients and healthy volunteers. Altogether tongue's MEPs are selectively impaired in PLS. This technique could be helpful for the diagnosis of PLS and to differentiate patients with PLS from those affected by upper motor neuron-predominant variants of ALS.